All Days 2007
DOI: 10.2118/106112-ms
|View full text |Cite
|
Sign up to set email alerts
|

Zeta Potential Altering System for Increased Fluid Recovery, Production, and Fines Control

Abstract: This paper presents a new zeta potential altering system that is based on an inner salt developed to enhance the water flowback recovery on borate and slick-water frac jobs. The system also aids in the control of fines. The mechanism of this system is to modify the zeta potential on particles such as frac sand from -50 mV, or coal from -28 mV, to more neutral values. This modification helps increase the potential for particle agglomeration and changes in the sand pack in the fracture to increase fluid recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 8 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…Acidizing (Huang et al 2002;Hibbeler et al 2003;Rozo et al 2007;Byrne et al 2009), a chemical stabilizer such as cationic or water-soluble polymers and ionic clay stabilizer (McLaughlin and Weaver 1982;Sharma 1996;Nguyen et al 2005), a coating with oil (Sharma 1996), and a zeta-potential-altering system (Kakadjian et al 2007) are some examples of suggested remediation techniques for this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Acidizing (Huang et al 2002;Hibbeler et al 2003;Rozo et al 2007;Byrne et al 2009), a chemical stabilizer such as cationic or water-soluble polymers and ionic clay stabilizer (McLaughlin and Weaver 1982;Sharma 1996;Nguyen et al 2005), a coating with oil (Sharma 1996), and a zeta-potential-altering system (Kakadjian et al 2007) are some examples of suggested remediation techniques for this problem.…”
Section: Introductionmentioning
confidence: 99%
“…The ZPAS does not modify the chemical structure of friction reducers and gelling systems such as nonionic, cationic, and anionic polyacrylamide and guar gums and derivatives, making it compatible with slick-water systems and borate-based crosslinked gels. The molecule is very stable in acid and caustic solutions except under extreme conditions 11 .…”
Section: Zeta Potential Altering Systemmentioning
confidence: 99%
“…Another mechanism used to remediate the formation damage is changing the surface charges of the porous media through a zeta potential altering system [17,18]; for this, some amine-based cationic surfactants [19] and some additives [20,21], such as potassium chloride, ammonium chloride, and tetramethylammonium chloride, have been studied because of their capacity to bind to the clay surface by exchanging cations with its layer resulting in its integration and neutralizing the negative charges on the clay surface [19]. Notably, the cetyl trimethyl ammonium bromide (CTAB) has been used due to the quaternary ammonium end, which provides to the porous media the positive charges, while the hydrocarbon chains supply a steric exclusion effect [22].…”
Section: Introductionmentioning
confidence: 99%